Working Hours and Productivity - Marion Collewet; Jan Sauermann (Institute of Labor Economics (IZA), 2017)
This paper studies the link between working hours and productivity using daily information on working hours and performance of a sample of call centre agents. We exploit variation in the number of hours worked by the same employee across days and weeks due to central scheduling, enabling us to estimate the effect of working hours on productivity. We find that as the number of hours worked increases, the average handling time for a call increases, meaning that agents become less productive. This result suggests that fatigue can play an important role, even in jobs with mostly part-time workers.
Keywords: J23; J22; M12; M54; 330; working hours; productivity; output; labour demand